Daily Activities of Two Potamidid Snails in the Mangrove Forest at Teluk Hurun, South Lumpung - Mirza Dikari K Wahono (Department of Forest Resources Conservation and Ecotourism - IPB University, 1991)
Daily activities of two Potamidid snails, Telescopiunl telescopiunz and Cm'thidea quadram were investigated at Teluk Hurun, South Lampung. T. relescopiunt occupied the muddy part of the mangrove area with a vely low frequency of occurence and were found aggregatively reaching 2 m height on Rluzopora spp.trees. BothT. telescopi ml and C. quadra!a were found in the mid and the rear zones.The result showed that the timing of activities of the two snails related to the tidal regime. The movement of T. tele.scop umis initiated both by low tide and tidal inundation. This finding suggests that the snails need moist condition to stimulate their activities. On the other hand, the activities of C. quadrara occured only during the high tide. The tree climbing habit of C. quadrara during the high tide appears to be associated with its respiratory system. There is a relation beetwen tidal level and the height above the substrate of snail a=regatlon and the percentage of marked snails on treeswith percentage of marked snails on the ground. It isconcluded that the distributionof the twosnailsis not onlydueto theirhabitat preferences (degree of shadiness and substrate condition)but also due to their daily activities.